2009
DOI: 10.1002/polb.21716
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dioctyl phthalate plasticization on the morphology and thermal, mechanical, and rheological properties of chemical crosslinked polylactide

Abstract: The tensile strength and thermal stability of polylactide (PLA) were significantly improved through chemical crosslinking. However, it became much more rigid and brittle. To obtain a material with good thermal stability and enhanced ability to plastic deformation, chemical crosslinked PLA with 0.5 wt % triallyl isocyanurate and 0.5 wt % dicumyl peroxide was blended with different contents of dioctyl phthalate (DOP). The advantage of using DOP is that it does not crystallize, has low glass transition temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 31 publications
2
22
0
1
Order By: Relevance
“…The present morphology trend of PLA/ESO blends could be similar to the trend reported by Yang et al (2009), where microvoids occurred when excess plasticizer was added. Yang and co-workers (2009) added dioctyl phthalate (DOP) plasticizer into crosslinked PLA.…”
Section: Morphology Characterizationsupporting
confidence: 89%
See 1 more Smart Citation
“…The present morphology trend of PLA/ESO blends could be similar to the trend reported by Yang et al (2009), where microvoids occurred when excess plasticizer was added. Yang and co-workers (2009) added dioctyl phthalate (DOP) plasticizer into crosslinked PLA.…”
Section: Morphology Characterizationsupporting
confidence: 89%
“…It is the phase separation that caused the insignificant reduction in Tg in the present work. Similarly, Yang et al (2009) and Kulinski et al (2006) reported minor decrease of Tg when the plasticizers DOP and poly (propylene glycol) (PPG) loading reached a certain amount where phase separation within PLA matrix occurred.…”
Section: Differential Scanning Calorimetry Analysismentioning
confidence: 91%
“…However, PEOX did not provide strong interfacial adhesion between two phases 16, 20. pMDI, as a strong interfacial modifier, reacted with the hydroxyl groups of PLA and SPC and the amine groups of SPC,20 establishing cross‐links between PLA and SPC which led to higher viscosity of the PLA/SPC blends 20, 24, 25. Therefore, the pressure drop was increased as addition of pMDI.…”
Section: Resultsmentioning
confidence: 99%
“…Yang et al [277] produced PLA cross-linked with 0.5 wt% triallyl isocyanurate (TAIC) and 0.5 wt% DCP, plasticized with dioctyl phthalate (DOP) plasticizer. Cross-linking helped in improving the thermal stability of PLA, and plasticization helped in dispersing the cross-linking agents.…”
Section: Plasticization Of Plamentioning
confidence: 99%
“…The T m of PLA also dropped from 179 to 161 C. Nonhomogeneous blends and phase separation were observed for 12.5% and 15% DOP in PLA. SEM micrographs obtained from fractured surfaces revealed DOP droplets in the PLA matrix at 15% DOP concentration (Figure 16.19) [277].…”
Section: Plasticization Of Plamentioning
confidence: 99%